Association of hematological and biochemical tests and complications after cardiovascular surgery - Leontina Graube, Sandra; Okaseski, Karen Rafaela; Felipin Ludvig, Bruna; Agnolleto Bewanger, Silvana; Lemes Lobo Bittencourt, Vivian; Colet, Christiane de Fátima; Roseli Winkelmann, Eliane (O Mundo da Saúde, 2022)
Cardiac surgery has postoperative complications of varying severities. Knowing the predictors of such complications can minimize risks and increase patient survival. However, studies address postoperative complications without any standardization of predictors of such complications. The objective of this study was to evaluate the association of hematological and biochemical parameters in the pre- and postoperative period with general clinical complications and those according to organ affected in the postoperative period of cardiac surgery. This is a cross-sectional, retrospective, analytical and documentary study. Inclusion criteria: Elective myocardial revascularization surgeries and/or valve replacements with a cardiopulmonary bypass from January to December 2017, in patients older than 18 years old, survivors until hospital discharge. Incomplete medical records were excluded. Ethical research precepts were followed. 194 patients were included. Preoperative leukocyte alterations increased the chance of postoperative complications by 8.24 times (p=0.039); high mean INR values in the first postoperative period were associated with complications (p=0.036); changes in creatinine (p=0.020) and INR (p=0.002) in the first and second postoperative period were associated with complications, in addition to changes in hemoglobin associated with cardiac complications on the third postoperative day (p≤0.001). There was an association between: leukocyte alteration prior to surgery and total postoperative complications; postoperative hematological and biochemical changes and complications in general and by affected organ. These results can support the development of risk indicators. This also indicates the need to improve monitoring of leukocyte levels, INR, hemoglobin, and creatinine, perceived as predictors of surgical complications.